Rearrangement of The Song Suwe Ora Jamu Using Fibonacci Numbers and Golden Ratio - Aliyatul Marzuqoh; Toheri Toheri; Indah Nursuprianah (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2021)
The rearrangement of the song suwe ora jamu uses the Fibonacci numbers and the golden ratio to facilitate the creation of music. The purpose of this study is to determine rearragement stages of the song suwe ora jamu using fibonacci numbers and golden ratio, to determine content of fibonacci numbers and golden ratio in the rearragement of the song suwe ora jamu, and to determine the difference in the beauty of the original song and rearrangement of the song suwe ora jamu uses fibonacci numbers and golden ratio. The method used in this research is mixed methods with a mixed-stage technique and a sequential exploratory strategy model. The results showed that: 1) 4 stages of rearrangement namely selecting the tone motif, determining the initial tone, determining the second tone using the initial tone or the previous tone as a reference, and determining the bar and its golden ratio, 2) analyzing the content of the Fibonacci numbers and the golden ration respectively are the song suwe ora jamu amounting to 32.1% and 61.804%, the first arrangement is 50% and 70.633% and the second arrangement are 46.2% and 98.887% and 3) the difference in the beauty of the original version of the song suwe ora jamu and the rear of the song suwe ora jamu using the Wilcoxon test is worth 0.000 <0.05, so it can be concluded that there is a difference in the beauty.Â